Journey of the Oriental Books and its Scientific Impact in Andalusia - Nouri Shukur, Huda (International Journal of Psychosocial Rehabilitation, 2020)
The attention of Muslims to books was very caring, and therefore they proudly wrote and acquired them. They highlighted a special interest in them in advance as they were one of the main pillars of the Arab Islamic civilization, which regarded books as a supporting ruler and assigned them as particularly important, surpassing all previous civilizations in the quantity and quality of their publication.Eastern books, which are coming to Andalusia, received the attention of its residents because they found in them the necessary knowledge, practical skills, wisdom, and literature. At the same time, special focus was paid to these books in the form of a generous reception, storage in special places, distinctive teachings, and memorization as sacred. Thus, a new (special) scientific direction was born in Andalusia and contributed to the development of the educational state program, creativity, and new books.The inhabitants of Andalusia were interested in copying Oriental books to facilitate their distribution throughout Andalusia and the use and study of their contents. At the same time, Andalusian scholars rewrote some of their profitable books in the form of simplification of their explanation, reduction, or study of special parts. On the other hand, it is noted that Eastern scholars also contributed to the scientific renaissance and intellectual movement of Andalusia at its peak (in the third, fourth, and fifth BH), as they transferred their knowledge and books to it.Andalusia has been the best resource for Islamic literature throughout the Abbasid period. Al-Andalus included diverse books, such as interpreted, linguistic and literary, biographical, origin, historical, experimental, scientific, etc.